Pembuatan Pathfinder (Panduan Pustaka) Layanan di Perpustakaan Universitas Andalas - Rahmayeni, Roza; Nurizzati, Nurizzati (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
Abstract This research studies about to create a pathfinder (service library) service in library Andalas University. The purpose is to describe the process of making pathfinders (service library) in the library of Andalas University. This research has been done by a descriptive method by visiting directly to Andalas University library to observe and do some interview. After the datum are analyzed, the conclusion explains some steps of creating pathfinder (service library) service in library Andalas University: (1) to conduct the observations and interviews; (2) to shoot a service workflow; (3) to design the service pathfinder products; (4) to arrange the service pathfinder. Keywords: create, Pathfinder, Library Service, library of Andalas University